Analisis Pengaruh Musim terhadap Konsentrasi Suspended Particulate Matter (SPM) dan Komponen Utama Kimia Air Hujan (KAH) - Latif, Abdul; Sunarno, Sunarno; Atmoko, Dwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aim to examine how level of Suspendet Particulate Matter (SPM) in the atmosphere and the chemical composition of rainwater vary due to seasonal influences during the 2020-2024 period at Semarang Central Java. Combined Principal Component Analisys (PCA) and wind direction mapping are used to track pollution patterns. This approach helps identify the primary sources of pollutans and understand their movement patterns during the rainy season compared to the dry season. The result show that SPM contrations are significantly higher during the dry season, with an average of 151.12 µg/m3, compared to the rainy season, which has an average of 107,25 µg/m3, due to reduced cleansing by rain and fewer rainfall events. Chemical analysis of rainwater revealed higher ion concentrations during the dry season, with NH4+ and SO42- dominating, whereas the rainy season was characterized by marine ions (Na+, Cl-) along with SO42-. PCA analysis identified two principal components for both seasons, explaining more than 80% of the total variance. During the rainy season, the dominant source is marine aerosols (PC1: 46.82%), while secondary anthropogenic sources form the second component. The dry season shows a complex mixture of marine, terrestrial, and biomass burning sources (PC1: 57.81%), with secondary anthropogenic aerosols remaining a consistent contributor. Windrose analysis confirms that westerly winds during the Asian monsoon season transport marine influences during the rainy season, while easterly winds during the Australian monsoon season transport terrestrial pollutants during the dry season. This demonstrates that the monsoon system acts as the primary controlling factor for air quality and atmospheric deposition in the study region. Keywords: Monsoon, PCA, Pollutans Rainwater, SPM